The Relationship Between Microbial Community and Breast Cancer - Song, Xuelian; Wei, Changran; Li, Xiangqi (Frontiers in Cellular and Infection Microbiology, 2022)
Breast cancer (BC) is the most common cancer in women and the leading cause of cancer-related deaths in women worldwide. Recent research studies have shown that the intestinal flora is related to the occurrence and progression of BC. Notably, some evidence identifies a unique microbial community in breast tissue, a site previously thought to be sterile. In addition, breast tumors have their own specific microbial community, distinct from normal mammary gland tissue, and all of them may result from intestinal flora. Some microbial community in breast tissue may lead to the occurrence and development of BC. This review focuses on the relationship between the microbial community and breast cancer, which will lay a solid theoretical foundation for further understanding the local microenvironment of BC and developing effective targeted therapeutic drugs.